The association between cardiac involvement and long‐term clinical outcomes in patients with Duchenne muscular dystrophy. (17th May 2022) - Cha, Jung‐Joon; Kim, In‐Soo; Kim, Jong‐Youn; Choi, Eui‐Young; Min, Pil‐Ki; Yoon, Young Won; Lee, Byoung Kwon; Hong, Bum‐Kee; Kwon, Hyuck Moon; Cho, Han Eol; Choi, Won Ah; Kang, Seong‐Woong; et al.
Abstract: Aims: Despite advances in contemporary cardiopulmonary therapies, cardiomyopathy remains the leading cause of death in patients with Duchenne muscular dystrophy (DMD). Also, the long‐term clinical outcomes of patients with DMD and cardiomyopathy is unknown. This study investigated long‐term clinical outcomes and their associated factors in patients with late‐stage DMD. Methods and results: A total of 116 patients with late‐stage DMD (age > 15 years) were enrolled in this retrospective study. All enrolled patients were followed up at a single tertiary referral hospital. LV systolic dysfunction was dichotomously defined as reduced [left ventricular ejection fraction (LVEF) ≤ 40%] vs. preserved [>40%] based on the initial echocardiographic result. The primary endpoint was all‐cause death. The secondary endpoint was a composite event defined as death or unexpected hospitalization due to cardiovascular reasons including chest pain, dyspnoea, and generalized oedema. The patients were divided into preserved ( n  = 84, 72.4%) and reduced LVEF groups ( n  = 32, 27.6%). The mean age was 20.8 ± 5.9 years, the mean disease duration, 8.8 ± 3.7 years, and the mean follow‐up duration, 1708 ± 659 days. For primary endpoint, the reduced LVEF group showed a lower rate of overall survival (Reduced LVEF vs. Preserved LVEF; 81.3% vs. 98.8%, log‐rank P  = 0.005). In the multivariable Cox regression analysis, brain‐natriuretic peptide (BNP) level (adjusted hazard ratio [HR] 1.088, 95% confidence interval [CI] 1.019–1.162, P  = 0.011) and diuretic use (adjusted HR 9.279, 95%CI 1.651–52.148, P  = 0.011) were significant predictors of all‐cause death in patients with DMD. For the secondary endpoint, the reduced LVEF group had a lower rate of freedom from composite events than the preserved LVEF group (65.6% vs. 86.9%, log‐rank P  = 0.005). In the multivariable Cox regression analysis, BNP level (adjusted HR 1.057, 95%CI 1.005–1.112, P  = 0.032) and diuretic use (adjusted HR 4.189, 95% CI 1.704–10.296, P  = 0.002) were significant predictors of the composite event in patients with DMD. Conclusions: Patients with DMD and reduced LVEF had worse clinical outcomes than those with preserved LVEF. BNP level and diuretic use were associated with adverse clinical outcomes in patients with late‐stage DMD, irrespective of LVEF.